2019
DOI: 10.3390/coatings9020092
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Al2O3 Coating on LiNi0.8Co0.1Mn0.1O2 Cathode Material for Enhanced Cycleability at Extended Voltage Ranges

Abstract: Ni-rich LiNi0.8Co0.1Mn0.1O2 oxide has been modified by ultrathin Al2O3 coatings via atomic layer deposition (ALD) at a growth rate of 1.12 Å/cycle. All characterizations results including TEM, SEM, XRD and XPS together confirm high conformality and uniformity of the resultant Al2O3 layer on the surface of LiNi0.8Co0.1Mn0.1O2 particles. Coating thickness of the Al2O3 layer is optimized at ~2 nm, corresponding to 20 ALD cycles to enhance the electrochemical performance of Ni-rich cathode materials at extended vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(71 citation statements)
references
References 46 publications
1
69
1
Order By: Relevance
“…Al 2 O 3 ) is often reported. [13,14] Other strategies include functional electrolyte additives, alternative solvents with higher oxidative stability, and core-shell or concentration gradient structures. [12,15,16,17] Lately, micron sized single crystalline layered oxides have gained attention as they can alleviate excessive surface exposure from grain boundary cracking.…”
Section: Introductionmentioning
confidence: 99%
“…Al 2 O 3 ) is often reported. [13,14] Other strategies include functional electrolyte additives, alternative solvents with higher oxidative stability, and core-shell or concentration gradient structures. [12,15,16,17] Lately, micron sized single crystalline layered oxides have gained attention as they can alleviate excessive surface exposure from grain boundary cracking.…”
Section: Introductionmentioning
confidence: 99%
“…This sets ALD apart from chemical bath deposition or line‐of‐sight techniques, such as physical vapor deposition, which create thicker films on the surface of particles but do not reach into pores and cracks of rough surfaces of the CAM secondary particles. For Ni‐rich NCMs and NCAs, the technique has been used to deposit Al 2 O 3 ,, LiAlO 2 , LiAlF 4 , Li 3 PO 4 and TiO 2 . However, many of the available ALD coating materials and routes are unexplored to date or have only been tested for low‐Ni CAMs.…”
Section: Coatingsmentioning
confidence: 99%
“…[ 15,16 ] Until now, scientists have made a lot of efforts and scientific research to improve the electrochemical characteristics, finally, the surface coating proved to be an effective method. It has been reported that coating inorganic compounds such as metal oxides (SiO 2 , [ 17 ] WO 3 , [ 18 ] Co 3 O 4 , [ 19 ] ZrO 2 , [ 20 ] ZnO [ 21 ] , and Al 2 O 3 [ 22,23 ] ), phosphates (Mn 3 (PO 4 ) 2 [ 24 ] ), and fluorides (AlF 3 [ 25 ] ) effectively improve the structural stability of the cathode. It can also inhibit the dissolution of transition metal ions in the electrode by avoiding direct contact between the electrode and the electrolyte, and it can also avoid the destruction of the material structure during charging and discharging.…”
Section: Introductionmentioning
confidence: 99%